FC047: RNA Sequencing of Microdissected Kidney Biopsies from IGA Nephropathy Patients. (3rd May 2022) - Levin, Anna; Schwarz, Angelina; Herthelius, Maria; Wennberg, Lars; Peter Barany, Franz; Bruchfeld, Annette; Witasp, Anna; Wernerson, Annika
Abstract: BACKGROUND AND AIMS: As the most common glomerulonephritis globally, mainly affecting younger adults and one of the most common causes of kidney failure [1 ], IgA Nephropathy (IgAN) poses an immense impact both on the individual and on the societal level. Here, we aimed to gain further molecular insight into the high interindividual variability of the clinical picture and disease progression by linking transcriptional profiling of IgAN-kidneys to clinical and histopathological data. METHOD: Kidney biopsies from patients with histopathologically verified IgAN/IgA vasculitis ( n  = 84) (IgAV) [57 males, median (range) age of 39 (4–89) years] and 11 living donors (LD) [six males, median (range) age of 37 (30–65) years] were manually microdissected into glomerular and tubulointerstitial fractions. RNA was extracted with RNeasy lipid tissue mini kit (Qiagen, Valencia, CA, US) and evaluated using the Bioanalyzer 2100 (Agilent, Santa Clara, CA, US). mRNA purification, conversion to cDNA, fragmentation and double-stranded cDNA synthesis, amplification and clean-up were performed using Illumina Stranded mRNA prep ligation protocol (Illumina Inc). Paired-end RNA sequencing was performed in three different batches (Illumina Novaseq 6000). Data pre-processing was done using Trim Galore (v.0.6.4). Reads were aligned to the Ensembl GRCh38 reference genome using STAR (v2.6.1d). Gene counts were obtained using featureCounts (v1.5.1). Quality control was made using MultiQC (v.1.7). Comparisons between groups were performed using Bioconductor package DESeq2 (v1.22.2) and gene set enrichment analysis using Bioconductor package fgsea. The biopsies were evaluated by experienced renal pathologists using the Oxford classification [2 ] and the Banff classifications [3 ]. Clinical data at time of biopsy and 5-year follow-up was retrieved from patients' files. Co-morbidity- and mortality data was extracted from the Swedish renal registry up to 19 years after the biopsy. RESULTS: Principal Component Analysis showed clear separation between diseased and LD kidney transcriptomes, as well as between glomerular and tubulointerstitial fractions. Top upregulated genes in glomeruli were associated with complement activation and fibrosis. In tubulointerstium, top genes were related to the immune system, including chemokines. Gene ontology enrichment analysis highlighted immune response and complement activation in both compartments. Additionally, cell membrane and mitochondrial activity were enriched in tubulointerstium. Linking bioinformatic results to clinical data at the time of biopsy, progress over time as well as to histopathological data in accordance with the Oxford classification system [2 ] is ongoing. CONCLUSION: This is, to our knowledge, the most comprehensive RNA sequencing performed on paired glomerular and tubulointerstitial tissue from patients with IgAN/IgAV. Initial bioinformatical analyses highlights biologically relevant processes involving different parts of the immune system. Our project has the potential to identify molecular processes associated with rapid disease progression and specific histopathological characteristics. This enables identification of patients with a more aggressive disease and individualized treatment depending on molecular profile, which would improve kidney survival and quality of life for patients suffering from IgAN/IgAV.